Things We've Learnt About Home Life - Taylor, Alex; Harper, Richard; Lindley, Siân; Sellen, Abigail; Banks, Richard; Downer, J.; Berger, Neeltje (Thing's We've Learnt About, 2016)
Things We’ve Learnt About..” is a publication from the Human Experience & Design team that summarises our work around a specific theme in a way that we hope is interesting, insightful and inspirational. And most importantly, succinct.